Pengembangan Kompetensi Guru dalam Pembelajaran PAI bagi Generasi Z - Sari Narulita; Rihlah Nur Aulia; M Rudi Barnansyah; Aminah Aminah; M Zaki as Suminar (Publikasi Pendidikan, 2019)
The current young generation or the so-called Z generation is a generation born after 2000 until now and is very attached to gadgets. The ease that they have in accessing media, unfortunately, is not accompanied by a strong filter ability to be able to sort and select the information they receive. Therefore, today's teachers need to prepare themselves by developing their competencies to handle it. The solution offered is the development of the competence of PAI (Islamic religious education) teachers to be able to understand their students, who generally come from Z generation so that the learning process of PAI becomes effective. This service activity aims to help teachers and prospective teachers in increasing their understanding, awareness, and strategies in creating a PAI learning process that is interesting for the Z Generation. The implementation of activities in the form of workshops related to effective communication between teacher and students, the urgency of PAI in shaping character, the introduction of the characteristics of the Z Generation and PAI learning strategies for the Z Generation and closed with a share and care session. The workshop was conducted using an interactive method, between speakers and participants and supported by an assembly of sharing and care that strengthens and enhances the experiences and insights of teachers and prospective teachers on how to handle the Z generation in the Islamic religious education learning process